PENINGKATAN MOTORIK KASAR SISWA SEKOLAH DASAR MELALUI PENERAPAN PERMAINAN BERBASIS MODEL PENDIDIKAN GERAK - Dimas Adi Saputra, Dimas Adi Saputra; Lukmannul Haqim Lubay; Eva Sri Gumilang (Universitas Negeri Medan, 2025)
This study aims to determine the effect of the application of games based on the motion education model on improving gross motor skills of elementary school students. The method used is quantitative with a quasi-experimental design. The sampling technique used purposive sampling involving two groups, namely the control group of 26 students and the experimental group of 29 students. The instrument used was the Basic Movement Ability Test (TGMD) through pretest and posttest. The results of the analysis showed that the average gross motor score of the experimental group increased from 61.93 to 79.41, while the control group only increased from 65.73 to 66.96. The paired samples t-test showed a significant increase in the experimental group, and the independent samples t-test showed a significant difference between the two groups Sig. 2-tailed = 0.000. Thus, games based on the movement education model are proven to be effective in improving gross motor skills and can be an alternative to fun and participatory physical learning.